PENGELOLAAN DESTINASI WISATA PANTAI PULO KODOK KOTA TEGAL - Putri Eryani, Desy; Maesaroh, Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Pulo Kodok Beach is one of the tourist destinations in Tegal City. Good management will have an impact of the welfare of community around the tourist attraction and can create sustainable tourism. This research is intended to determine the management of Pulo Kodok Beach tourist destinations which is managed by Tourism Awareness Community (Pokdarwis). This research uses a qualitative descriptive research method with data collection through observation, interviews, and documentation. This research enforce a snowball sampling technique. The research results show that the implementation function in managing the Pulo Kodok Beach tourist destination is not yet optimal. This can be seen that the lack of budget is an obstacle for Pokdarwis in managing attractions, accessibility and amenities. The training attended by the management has not able to improve the skills of human resources. Pokdarwis has not been optimal in promoting Pulo Kodok Beach. Recommendations that can be given are that Pokdarwis members can take part in various tourism training, Regarding the lack of budget, Pokdarwis can use a priority scale system in managing tourist destinations or collaborate with investors. Pokdarwis also needs to empower young people around tourist attractions to promote Pulo Kodok Beach by utilizing social media.